Regularity to a Kohn-Laplace Equation with Bounded Coefficients on the Heisenberg Group (Journal of Mathematical Study, 2020)
In this paper, we concern the divergence Kohn-Laplace equation$$\sum\limits_{i = 1}^n {\sum\limits_{j = 1}^n {\left( {X_j^*({a^{ij}}{X_i}u) + Y_j^*({b^{ij}}{Y_i}u)} \right)} } + Tu = f - \sum\limits_{i = 1}^n {\left( {X_i^*{f^i} + Y_i^*{g^i}} \right)}$$ with bounded coefficients on the Heisenberg group ${{\mathbb{H}}^n}$, where ${X_1}, …, {X_n},{Y_1}, …, {Y_n}$ and $T$ are real smooth vector fields defined in a bounded region $Ω \subset {\mathbb{H}^n}$. The local maximum principle of weak solutions to the equation is established. The oscillation properties of the weak solutions are studied and then the Hölder regularity and weak Harnack inequality of the weak solutions are proved.
Keywords: Heisenberg group; Kohn-Laplace equation; local maximum principle; Hölder regularity; weak Harnack inequality.